2021
DOI: 10.5812/hepatmon.118640
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Platelet to White Blood Cell Ratio and 30-Day Prognosis of Patients with Acute-on-Chronic Liver Failure

Abstract: Background: Acute-on-chronic liver failure (ACLF) is always associated with thrombocytopenia or leukocytosis. Therefor the platelet to white blood cell ratio (PWR) in ACLF patients is always reduced. Objectives: Here, we assessed the relationship between PWR and prognosis in ACLF patients. Methods: A retrospective cohort of 415 patients, including 100 patients that were diagnosed of chronic hepatitis B, 104 patients suffered of HBV-related liver cirrhosis and 211 patients suffered of HBV-related ACLF, was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Platelets are necessary for targeting WBCs at inflammation sites [41]. Platelets also promote liver regeneration by secreting platelet-derived growth factors and hepatocyte growth factors [42]. So, diminished platelet count can hinder hepatocyte regeneration and augment liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are necessary for targeting WBCs at inflammation sites [41]. Platelets also promote liver regeneration by secreting platelet-derived growth factors and hepatocyte growth factors [42]. So, diminished platelet count can hinder hepatocyte regeneration and augment liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…This study also identified the plausible factor that decreased the PWR, there were ascites and infection (p = 0.003). 2 Retrospective cohort study from Jia et al included 433 ACLF-related HBV patient and showed significantly lower PWR than healthy control. This study also showed that there was moderate positive correlation between PWR and RBC (r = 0.2348, p < 0.0001) and HBV DNA (r = 0.1887, p < 0.001) in ACLF patient.…”
Section: Role Of Pwr In Predict Mortality In Aclf Hepatitis B-cirrhot...mentioning
confidence: 99%
“…The decrease peripheral platelet count is associated with liver fibrosis, hypersplenism, increased destruction of platelet, decreased platelet production, decreased thrombopoietin production, antiplatelet antibodies, disseminated intravascular coagulation, translocated toxin, and other gut-derived substance. 2,10,11 Additionally, there is additional mechanism for increased platelet destruction in chronic liver disease, which is the effect of elevated portal pressure. Thrombocytopenia can further aggravate liver damage and promote the progression of liver cirrhosis by decreasing the level of platelet-derived growth factor and hepatocyte growth factor.…”
Section: Mechanism Of Pwr In Predicting Mortality In Aclfmentioning
confidence: 99%
See 2 more Smart Citations